2022
DOI: 10.3390/cryst12040547
|View full text |Cite
|
Sign up to set email alerts
|

Fast Lead-Free Humidity Sensor Based on Hybrid Halide Perovskite

Abstract: An environmentally friendly analog of the prominent methylammonium lead halide perovskite, methylammonium bismuth bromide (MA3Bi2Br9), was prepared and investigated in the form of powder, single crystals and nanowires. Complete characterization via synchrotron X-ray diffraction data showed that the bulk crystal does not incorporate water into the structure. At the same time, water is absorbed on the surface of the crystal, and this modification leads to the changes in the resistivity of the material, thus maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This compression leads to an increased overlap between the Bi 6s/6p and Br 4p states, resulting in a smaller bandgap. [ 14f,15a,17b,18 ] After Ag incorporation in Cs 3 Bi 2 Br 9 , the absorption edge of Cs 2 AgBiBr 6 is significantly shifted toward higher wavelengths, indicating the reduction in the optical bandgap. The involvement of Ag atom orbitals has contributed to the band edges of Cs 2 AgBiBr 6 , thereby increasing the electronic dimensionality compared to the original Cs 3 Bi 2 Br 9 .…”
Section: Resultsmentioning
confidence: 99%
“…This compression leads to an increased overlap between the Bi 6s/6p and Br 4p states, resulting in a smaller bandgap. [ 14f,15a,17b,18 ] After Ag incorporation in Cs 3 Bi 2 Br 9 , the absorption edge of Cs 2 AgBiBr 6 is significantly shifted toward higher wavelengths, indicating the reduction in the optical bandgap. The involvement of Ag atom orbitals has contributed to the band edges of Cs 2 AgBiBr 6 , thereby increasing the electronic dimensionality compared to the original Cs 3 Bi 2 Br 9 .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Djokic et al produced a more expected MA 3 Bi 2 Br 9 material, with 2D layered structure belonging to the space group P% 3m1, similar to previous studies on bismuth and antimony halide perovskites. 43,44 It is also unlike the crystal structure of methylammonium bismuth iodide, which usually possesses a structure in which two face-sharing octahedra form the main part of the repeating unit. 45 This difference is likely due to the synthesis method of the single crystals, a slow, solvent evaporation-based method that allows plenty of time for the crystallisation of the material to include the DMSO solvent.…”
Section: Methylammonium Bismuth Bromidementioning
confidence: 99%
“…Other solvents to DMSO should be explored, as the formation of the DMSO solvate crystal into a zero-dimensional structure, as opposed to the previously reported 3-D crystal structures, likely hampers performance. 43,44…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…[ 10 , 11 , 12 , 13 ]. More interestingly, in recent years, perovskites have begun to rise as a promising sensor material in detecting NO 2 , oxygen, ozone, ammonia, sulfur dioxide, humidity, organic vapors [ 9 , 14 , 15 , 16 , 17 , 18 , 19 ], etc. For instance, Fang et al in 2016 demonstrated that methylammonium lead tribromide (MAPbBr 3 ) single crystal showed an ultrahigh sensitivity toward the environmental atmosphere, including oxygen and water vapor [ 16 ].…”
Section: Introductionmentioning
confidence: 99%